Dynamic mathematical modelling of free fatty acid accumulation in fresh oil palm fruit (Elaeis guineensis jacq.) - Etsu, Shehu Umar (2019)
Crude palm oil (CPO) is extracted from the fleshy mesocarp of the oil palm fruits, (Elaeis guineensis). The fruit has to undergo several thermo-mechanical processes before the oil can be extracted. However, the oil-bearing mesocarp of the fruit contained an endogenous enzyme (lipase), which is activated upon injury/bruised. The hydrolytic activity of the enzyme leads to the accumulation of free fatty acid (FFA) which is a major quality index of CPO. Researches have shown that over 2% of fresh fruit bunches(FFB) arriving at the mill are bruised and the bulkiness coupled with the close-knitted nature of the FFB causes ineffective heat distribution/penetration into the inner layers of the fruits during the steam sterilization process, which is aimed in inactivation of the enzyme. Hence, the need to explore alternative medium of heat transfer. Heating of the extracted CPO with high moisture content to facilitate handling in the mill triggered up thermal hydrolysis at a temperature above 100oC (373 K). All these phenomena simultaneously led to poor palm oil quality. Therefore, a method for the quantification of a bruise was developed and used for this study. Bruise volume, storage temperature and time were found to have a significant effect (P<0.05) on FFA accumulation in oil palm fruits. Dynamic simulation of FFA in bruised fruits was used to predict the optimum temperature for FFA accumulation in bruised fruit to be 31oC (304 K). The GC-MS analysis of extracted CPO from bruised fruit heat-treated in chlorinated water indicates the formation of chlorinated fatty acids (Palmitic acid chloride and Lauric acid chloride). A wounding assay of the endogenous lipase in palm fruit was carried out to quantified in-vivo activity of the enzyme and the FFA accumulation in the fruitlets. A time-dependent heat penetration simulation was also conducted using a COMSOL Multi physics software along with the development of kinetic models for thermal inactivation of lipase and thermal hydrolysis of CPO. The model equations were solved and the parameters of the model estimated using gPROMS Model Builder. The two-way analysis of variance (ANOVA) shows that treatment duration and temperature had significant (P < 0.05) effect on the residual lipase activity. The inactivation kinetics of lipase was found to be a non-elementary reaction in which initial rate constant, k0dec and inactivation energy, Edec were estimated to be 0.035 U-0.85/kg-mes-0.85·min and 153052 kJ/kmol, respectively. The predicted residual activity fitted very well to the experimental data with relative root mean square error (rRMSE) between 0.19% and 1.17%. The important parameters for the thermal hydrolysis model estimated were activation energy, E (57554 kJ/kmol) and a frequency factor of reaction, k0T (2.14×10-6 m3/kmol·min). The relative root means square error (rRMSE) between the measured and the predicted FFA accumulation is between 1.92% and 31.98%. This indicates a satisfactory fit between the experimental and the predicted values. The sensitivity analysis of the developed models (bruise, thermal inactivation of lipase and thermal hydrolysis) revealed that they are sensitive to the selected parameters kcat, nb, k0dec, nd, nw, nT and n. These kinetic models provided a basic understanding of the mechanism of FFA accumulation in palm fruits and CPO during handling and processing and may be a useful tool in further re-designing and quality improvement of the industrial processes of crude palm oil extraction. However, to mitigate against associated problems of the current steam sterilization, hot water sterilization should be explored.